Low-Dose Aspirin for the Prevention of Preterm Delivery in Nulliparous Women With a Singleton Pregnancy (ASPIRIN): A Randomized, Double-blind, Placebo-Controlled Trial. Issue 6 (June 2020) - Hoffman, Matthew K.; Goudar, Shivaprasad S.; Kodkany, Bhalachandra S.; Metgud, Mrityunjay; Somannavar, Manjunath; Okitawutshu, Jean; Lokangaka, Adrien; Tshefu, Antoinette; Bose, Carl L.; Mwapule, Abigail; Mwenechanya, Musaku; Chomba, Elwyn; et al.
Abstract : (Abstracted from Lancet 2020;395:285–293) Preterm birth, or delivery before 37 weeks, is one of the most common causes of infant mortality. New evidence has shown that women who take low-dose aspirin (81 mg) may be at lower risk of preeclampsia.